Reliable solution processed planar perovskite hybrid solar cells with large-area uniformity by chloroform soaking and spin rinsing induced surface precipitation - Yann-Cherng Chern; Hung-Ruei Wu; Yen-Chu Chen; Hsiao-Wen Zan; Hsin-Fei Meng; Sheng-Fu Horng (AIP Advances, 2015)
A solvent soaking and rinsing method, in which the solvent was allowed to soak all over the surface followed by a spinning for solvent draining, was found to produce perovskite layers with high uniformity on a centimeter scale and with much improved reliability. Besides the enhanced crystallinity and surface morphology due to the rinsing induced surface precipitation that constrains the grain growth underneath in the precursor films, large-area uniformity with film thickness determined exclusively by the rotational speed of rinsing spinning for solvent draining was observed. With chloroform as rinsing solvent, highly uniform and mirror-like perovskite layers of area as large as 8 cm × 8 cm were produced and highly uniform planar perovskite solar cells with power conversion efficiency of 10.6 ± 0.2% as well as much prolonged lifetime were obtained. The high uniformity and reliability observed with this solvent soaking and rinsing method were ascribed to the low viscosity of chloroform as well as its feasibility of mixing with the solvent used in the precursor solution. Moreover, since the surface precipitation forms before the solvent draining, this solvent soaking and rinsing method may be adapted to spinless process and be compatible with large-area and continuous production. With the large-area uniformity and reliability for the resultant perovskite layers, this chloroform soaking and rinsing approach may thus be promising for the mass production and commercialization of large-area perovskite solar cells.